Copper and iridium conjugate addition – cyclisation processes; domino reactions - Solana González, Jorge (The University of Edinburgh, 2015)
Asymmetric conjugate addition of bis(pinacolato)diboron followed by aldol cyclisation of enone diones under the action of a chiral copper catalyst has been developed.This enantioselective process, using a chiral bisphosphine as ligand, allows the formation of bicyclic alcohols with four contiguous stereocentres in high diastero- and enantioselectivity. This catalytic system has been applied to the parallel kinetic resolution of a racemic β- ketoamide. Further functionalization of the bicyclic alcohols synthesised was also possible. A domino addition of arylboronic acids and cyclisation of alkynones via an undescribed iridium 1-4-migration process has been developed. A range of tricyclic compounds using a variety of arylboronic acids have been synthesised in good yields and high diasteroselectivity. The use of chiral bisphosphine ligand together with an iridium salt allows the formation of enantioenriched compounds in moderate yield.
Keywords: domino reactions; iridium; copper; borylation